Pegylated Insulin-Like Growth Factor 1 attenuates Hair Cell Loss and promotes Presynaptic Maintenance of Medial Olivocochlear Cholinergic Fibers in the Cochlea of the Progressive Motor Neuropathy Mouse - Bieniussa, Linda; Kahraman, Baran; Skornicka, Johannes; Schulte, Annemarie; Voelker, Johannes; Jablonka, Sibylle; Hagen, Rudolf; Rak, Kristen (Frontiers in Neurology, 2022)
The progressive motor neuronopathy (pmn) mouse is a model of an inherited motor neuronopathy disease with progressive neurodegeneration. Axon degeneration associates with homozygous mutations of the Tbce gene encoding the tubulin chaperone E protein. Tbce is responsible for the correct dimerization of alpha and beta tubulin. Strikingly, the pmn mouse also develops a progressive hearing loss after normal hearing onset, characterized by degeneration of the auditory nerve and outer hair cells (OHC) loss. However, the development of this neuronal and cochlear pathology is not fully understood yet. Previous studies with pegylated Insulin-like Growth Factor 1 (peg-IGF-1) treatment in this mouse model have been shown to expand lifespan, weight, muscle strength and motor coordination. Accordingly, peg-IGF-1 was evaluated for an otoprotective effect. We investigated the effect of peg-IGF-1 on the auditory system by treatment starting at postnatal day 15 (p15). Histological analysis revealed positive effects on OHCs synapses of medial olivocochlear (MOC) neuronal fibers and a short-term attenuation of OHC loss. Peg-IGF-1 was able to conditionally restore the disorganization of OHC synapses and maintain the provision of cholinergic acetyltransferase in presynapses. To assess auditory function, frequency-specific auditory brainstem responses and distortion product otoacoustic emissions were recorded in animals on p21 and p28. However, despite the positive effect on MOC fibers and OHC, no restoration of hearing could be achieved. The present work demonstrates that the synaptic pathology of efferent MOC fibers in pmn mice represents a particular form of "efferent auditory neuropathy." Peg-IGF-1 showed an otoprotective effect by preventing degeneration of OHCs and efferent synapses. However, enhanced efforts are needed to optimize the treatment to obtain detectable improvements in hearing performances.